Understanding climate change awareness and adaptation measures in urban settings - Hue, Nguyen Thi; Antriyandarti, Ernoiz (Social, Ecology, Economy for Sustainable Development Goals Journal, 2024)
Backgorund: Extreme weather events, such as flooding and droughts, are becoming more common, posing significant challenges to human existence, economic growth, and the natural environment. This research aims to provide a comprehensive understanding of climate change awareness and adaptation measures among adolescents and local people in Surakarta, Indonesia. The study seeks to assess how the local population perceives and responds to climate change, as well as to identify factors that make communities vulnerable to severe weather events. By exploring these factors, the study aims to shed light on the underlying causes of vulnerability and inform the development of effective adaptation and mitigation strategies. Method: The research methodology involves the use of structured questionnaires and surveys to collect data from 100 respondents in Surakarta. Statistical analysis, including regression analysis, is employed to assess the relationship between various demographic factors and climate change awareness. Demographic factors such as age, education level, and income are evaluated to understand their impact on climate change perception and responsiveness. Findings: The findings of the study highlight the importance of enhancing climate change knowledge among adolescents and local residents and underscore the need for targeted adaptation measures to address the unique challenges faced by urban communities in Surakarta. Conclusion: Overall, this study contributes to the broader understanding of climate change adaptation and resilience-building efforts in urban settings and provides valuable insights for policymakers, researchers, and community stakeholders working in the field of climate change mitigation and adaptation. Novelty/Originality of this article: Using a structured survey, this study assessed climate change awareness and adaptation measures among adolescents and residents. The findings highlight the importance of improving knowledge about climate change and developing appropriate adaptation strategies for urban communities.